Religion as a Source of Islamic Ethics and its Impact on the Islamic Accounting System - Suryadi , Hasdi (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The Islamic religion teaches about ethics and shows how religion shapes the Islamic accounting system and the ethical behavior of Muslim accountants. Cultural differences are becoming an increasingly important factor to be taken into account in running a business. They are also the subject of scientific research, for example in the context of their influence on the development of accounting systems in various cultural circles. Relevant reference literature, Al-Qur’an and Hadith were used for qualitative analysis which was carried out by induction and deduction methods. The analysis conducted shows that even though the scope of the code of ethics is in a Muslim-majority country, Indonesia, its message is reinforced by the Islamic religion which is seen as a source of law as well as professional ethics. That is, the legal sanctions given to violators of the rules are accompanied by the fear of punishment from Allah SWT on the Day of Judgment. It is hoped that this article will fulfill an informative role, enabling readers to understand the reasons for some of the differences in understanding ethical issues and ways of doing business in an Islamic cultural environment.